Evaluation of mortality and morbidity in patients with secondary peritonitis using predictive score of mortality in perforated peptic ulcer - Kumar, Navin; Sahu, Shantanu Kumar; Bedi, Karamjot Singh (International Surgery Journal, 2017)
Background: Gastrointestinal tract perforation is one of the common surgical emergency all over the world. Menekse et al devised POMPP score (predictive score of mortality in perforated peptic ulcer) to predict the morbidity and mortality in peptic ulcer perforation. The objective of this study was to assess the validity of POMPP score in peptic ulcer perforation and to assess its usefulness in gastrointestinal perforation due to causes other than the peptic ulcer. Methods: Fifty consecutive cases, who had undergone exploratory laparotomy for gastrointestinal perforation peritonitis, were included in the study. “These patients were assessed at the time of admission on the basis of Age >65 years, BUN >45mg/dl (Blood Urea Nitrogen) and Albumin <1.5g/L and a score of 1 point each had been given”. The total score was compared with the outcome of the disease in relation with mortality. Results: In our study, 42% of gastrointestinal perforation were due to peptic ulcer, 22 % due to small bowel perforations (18% Ileal and 4 % Jejunal), 14 % due to trauma and 22 % due to miscellaneous causes. Morbidity is common after gastrointestinal perforation and it ranges from 17-63% whereas mortality ranges from 6-14%. Conclusions: POMPP score is easy and valid scoring system for peptic ulcer perforation. Early detection of high risk peptic perforation cases, allow other supportive treatment modality apart from surgery which can decrease the mortality. However, this score is not valid in perforation due to causes other than peptic ulcer.